Sorbent-incorporated dipstick for direct assaying of proteases - Klisara, Nevena (2022)
Efficient removal of interferents from complex matrices would significantly improve the performance of state of the art dipstick assays. Herein, we evaluate a graphitized carbon black (GCB)-incorporated dipstick, a configuration that has not been explored before, for reliable and facile on-site analysis of complex matrices. Carrot juice, a highly pigmented sample matrix, is chosen for evaluating the retention of interferents within the sorbent-incorporated cleanup pad on the dipstick. A peptide with a specific cleavage site for botulinum neurotoxin A light chain (BoNT/A LC), a model protease for validation of the proposed dipstick assay, is incubated with the test samples containing BoNT/A LC. Subsequently, the BoNT/A LC digested substrate and sample matrix flow vertically through the GCB-deposited cleanup pad within which the matrix interferents are captured, while the substrate, with a minimum of interferents, continues to flow toward a conjugation pad for labelling with Europium particles. Finally, the cleaved and uncleaved substrates flow toward a detection zone, where they bind to the test line producing a pinkish band which is not visible in the absence of GCB incorporation. The dipstick assay yields a LOD of 0.1 nM (5 ng/mL) of BoNT/A LC in carrot juice, within 20 min. The reported approach enables detection of proteases in a wide range of matrices upon incorporation of appropriate sorbents, ultimately aiming to exclude tedious laboratory-based sample pre-treatment protocols. Thus, merging extraction, cleanup, and pre-concentration steps with a sensitive optical detection approach is an attractive strategy for on-site assaying in complex matrices. Graphical abstract.